The winter of Frankie Machine - Winslow, Don, 1953-; Boutsikaris, Dennis (Ashland, Or. : Blackstone Audiobooks, 2006)
Frankie Machianno is a late-middle-aged ex-surf bum who runs a bait shack on the San Diego waterfront. He's also a retired Mafia hit man. But a favor being called in now by the local boss is one Frank can't refuse, and soon he's sucked back into the treacherous currents of his former life. Someone from the past wants him dead. He has to figure out who and do it fast.
Compact discs.
Read by Dennis Boutsikaris.
Keywords: Surfers -- Fiction; Mafia -- Fiction; California -- Fiction; Mystery fiction; Detective and mystery stories; Sound recording; Audiobooks; Compact discs